IMPLEMENTATION OF THE BALANCED SCORECARD-BASED STRATEGY TO IMPROVE SCHOOL QUALITY AT SD NEGERI 2 SAREE, ACEH BESAR DISTRICT - Muzakkir, Muzakkir; Kasmini, Lili; Musdiani, Musdiani; Amalina, Zahraini (Jurnal Visipena, 2025)
This study aims to conduct an in-depth analysis of the implementation of strategic planning using the Balanced Scorecard as an innovative approach to improving educational quality at SD Negeri 2 Saree, Aceh Besar District. The Balanced Scorecard is a strategic management framework that emphasizes a balanced focus across four organizational perspectives: financial, stakeholder (customer), internal processes, and learning and growth. This research employs a descriptive qualitative approach, using data collection methods including direct observation, in-depth interviews with the principal, teachers, and school committee members, as well as document analysis of school planning records. The findings show that all four Balanced Scorecard perspectives have been systematically and consistently integrated into the school's strategic planning. The financial perspective ensures efficient budget allocation; the stakeholder perspective reflects the needs and satisfaction of parents and students; the internal process perspective enhances operational effectiveness; and the learning and growth perspective promotes professional development and a sustainable learning culture. The implementation of the Balanced Scorecard-based strategy has effectively fostered synergy among school components, enhanced transparency and accountability, and enabled the delivery of adaptive educational services. These findings provide a valuable contribution to quality management practices in primary education and may serve as a model for other schools seeking a structured and measurable approach to strategic planning.